PENGGUNAAN MEDIA PELATIHAN BOLA MODIFIKASI TERHADAP HASIL PRESTASI SEPAK SILA PADA EKSTRAKURIKULER SEPAK TAKRAW (STUDI PADA PESERTA EKSTRAKURIKULER SMP NEGERI 3 SRENGAT KABUPATEN BLITAR) - SUSANA, ARI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract A provision of training media to suit the training needs that are expected to handle the adversity of cross kick techniques extracurriculer the game of sepak takraw, one of them is by using a modification of training media, such as balloons media, hanging balls media, plastic ball media, and the ball media the is not standard, where students are given the modifications in training media students will feel no fear of real sepak takraw which actually is a hard sport and the students are likely to feel pain when kicking the ball, the nature of the modification is to ease light and the media that can be played easily by students which will facilitate the movement of students doing a good cross kick and student will feel happy and not scared anymore to do a cross kick, so the modification the training media aims to facilitate of achievement wich expected good and optimum. The goals of this research is learning result to know about: the influences of using modificated media for the cross kick training result in sepak takraw in extracurriculer participant Junior High School 3 Srengat-Blitar and how high is the increase of cross kick achievement result by using modificated media in participant of extracurriculer Junior High School 3 Srengat-Blitar. This research is a kind of experiment research with descriptive quantitative approach with design One Group Pre-test and Post-test. Population of this study are the students participaed in extracurriculer Junior High School 3 Srengat-Blitar who were 30 students, samples taken throughout the student who participating in extracurriculer Junior High School 3 Srengat-Blitar who were 30 students. This research analysis use t-test similar. The result is: The use of modificated training media influences the training result of cross kick in takraw in the participant of extracurriculer at the Junior High School 3 Srengat-Blitar. From t-test is result point t count 9,14> t table 2,045 and by using modificated training media can increase the participant extracurriculer Junior High School 3 Srengat-Blitar achievement result of cross kick in takraw at the as big as 28,77%. Keywords : media training ball modification, cross kick.